Dynamics of Size and Value Factors in Stock Returns : Evidence from India - Balakrishnan, A.; Maiti, Moinak (Indian Journal of Finance, 2017)
This paper evaluated the cross sectional relationship between firm characteristics : size and value with risks and expected returns in the Indian stock market on different horizon of time from previous studies. Furthermore, the study deployed different breakpoints for market capitalization (median, market capitalization, and BSE breakpoints) and price to book ratio (equal weighted and Fama-French breakpoints). Motivation for using different breakpoints for market capitalization and price to book ratio was to check the sensitivity of the results. Average stock return patterns, residual graphs, R2, Fama - MacBeth cross sectional test, and GRS test confirmed the inability of both CAPM and Fama-French three factor model to capture the risk-return relationship. Furthermore, all test results confirmed that there was a strong size effect and mild value effect in the Indian stock market. Finally, the study found that MC breakpoints were sensitive to the results, but P/B breakpoints were not sensitive to the results.